Rapid Pyrolysis of Biomass, Biomass Components and Biomass Derived Products in a Drop-tube Furnace at High Temperature - Deng, Changya (Curtin University, 2020)
This thesis focuses on soot formation during biomass rapid pyrolysis at high temperature (1300 °C). A new method has been developed for collection of size-segregated soot samples. The experimental program systematically covers the effect of feeding rate on soot formation, characteristics of soot formed, properties of inorganic species in soot, soot formation during rapid pyrolysis of biomass components and biomass-derived products (bio-oil and biochar).